FAKTOR PENDORONG KEBERHASILAN SISWA DALAM BELAJAR GEOGRAFI KELAS XI SMA NEGERI 1 BAYANG TAHUN AJARAN 2013/2014 - Susanti, Iya - (STKIP PGRI Sumbar, 2014)
This study aimed to obtain data, information and description of the student success in learning geography, which in terms of: (1) student interest in learning (2) Student Motivation in Learning. (3) The efforts of teachers in teaching. This type of research is classified in a descriptive study. The population in this study were all students of class XI of SMAN 1 Bayang year 2013/2014 school year, amounting to 86 people. The sampling technique used in this study a total random sampling technique with a sample of 86 people. The data analysis technique used in this research is to use a percentage formula. The results of this study found that: (1) To encourage interest in improving student learning outcomes in geography class XI of SMAN 1 Bayang is less good, with a percentage of 69% of students strongly agreed and agree expressed an interest in the study of geography, (2) Student motivation can be encouraging in improving learning outcomes in geography class XI of SMAN 1 Bayang is less good, with a percentage of 62% of students stated strongly agree and agree motivated in learning geography, (3) Efforts in teaching students teachers can encourage in improving learning outcomes in geography class XI SMAN 1 Bayang is unfavorable, the percentage of 51% of students stated strongly agree and agree to have the efforts of teachers in teaching geography.